Experimental Investigation on Machinability of Titanium Alloy by Laser-Assisted End Milling - Dong-Hyeon Kim; Choon-Man Lee (Metals, 2021)
The Machining of titanium alloys is challenging because of their high strength, low thermal conductivity, high chemical reactivity, and high stresses at the cutting tool edges. Laser-assisted machining is an effective way to improve the machinability of titanium alloys. This paper presents an experimental investigation of the machinability of cutting force and surface roughness in laser-assisted end milling of titanium alloy Ti-6Al-4V. The absorptivity of Ti-6Al-4V was determined by conducting preheating experiments using a high-power diode laser with a wavelength of 940–980 nm. A thermal analysis was performed using the finite element method to predict temperature distribution. The depth of cut was determined where tensile strength decreased sharply, and the predicted surface temperature is presented in the analysis results. The experiments were performed with conventional machining and laser-assisted machining. Surface roughness, tool wear, and cutting force were evaluated. In contrast to the results of conventional end milling, laser-assisted end milling improved surface roughness. Moreover, laser-assisted end milling proved more effective than conventional end milling in terms of cutting tool damage. Our results proved that heat assistance significantly influenced the magnitude of the cutting forces—while the actual reduction in forces varied slightly depending on the force component, cutting tool, and cutting conditions, force components showed a reduction of roughly 13–46%.